Simultaneous quantitation of multiple contraceptive hormones in human serum by LC-MS/MS - Blue, Steven W. (Contraception, 2018)
OBJECTIVE: To develop a method to simultaneously quantify five commonly used hormonal contraceptives (HC) and 2 endogenous sex steroids by liquid chromatography-tandem triple quadrupole mass spectrometry (LC-MS/MS) and apply this method to human serum samples. STUDY DESIGN: We developed a method to simultaneously analyze ethinyl estradiol (EE2), etonogestrel (ENG), levonorgestrel (LNG), medroxyprogesterone acetate (MPA), and norethisterone (NET), along with estradiol (E2) and progesterone (P4) in human serum for a Shimadzu Nexera-LCMS-8050 LC-MS/MS platform. We analyzed serum collected from women self-reporting use of oral contraceptives, contraceptive implants or injectable contraceptives (n=14) and normally cycling women using no HC (n=15) as well as pooled samples from women administered various HC (ENG, n=6; LNG, n=14; MPA, n=7; NET, n=5). RESULTS: Limits of quantitation were 0.010 ng/ml for E2, EE2, and P4; 0.020 ng/ml for ENG, LNG, and MPA; and 0.040 ng/ml for NET. Precisions for all assays, as indicated by coefficient of variation (CV) were less than or equal to 12.1%. Accuracies for all assays were in the range of 95–108%. Endogenous hormone values obtained from analysis of human serum samples are in agreement with levels previously reported in the literature for normally cycling women as well as for women taking the appropriate HC. CONCLUSIONS: We have developed a robust, accurate, and sensitive method for simultaneously analyzing commonly used contraceptive steroids and endogenous sex steroids in human serum. IMPLICATIONS: This analytical method can be used for quantitating contraceptive steroid levels in women for monitoring systemic exposure to determine drug interactions, nonadherence, misreporting, and proper dosing.